Biological bases on the concept of hypothalamic-pituitary 'imprinting - Barbarino, Antonino; De Marinis, Laura (Medicina e Morale, 2024)
Endocrine control of genital development and function is exerted by the hypothalamic-pituitary-gonadal axis. The initial signal comes from the hypothalamus which, by secreting a recently isolated and synthesised peptide hormone (GnRH), stimulates the pituitary secretion of the gonadotropins FSH and LH. These in turn control the secretion of gonadal steroids that are different for the male (testosterone of testicular origin) and the female (oestrogen of ovarian origin).